Evaluating the effects of simulated interprofessional teaching on the development of clinical core competence in nursing students: a mixed methods study - Xin-yi Zhou; Yan-feng Wang; Chun-xia Dou; Xiao-ying Tian; Jin Su; Yan-ya Chen; Feng-xia Yan; Qiao-hong Yang; Wenru Wang (BMC, 2022)
Abstract Background While single-method studies have reported on the effectiveness of simulated interprofessional teaching, our understanding of its full effects remains incomplete. Teaching design also provides no relevant theoretical guidance, which reduces the scientific quality and rigor of research. The purpose of this work was to study the effects of the simulated interprofessional education (SIPE) teaching model based on the 3P theory on the course of "Clinical Critical Thinking Training" through a convergent mixed method, and to provide the basis for future teaching design. Methods A convergent mixed-method design was used, which consisted of a survey and a semi-structured interview. Data collection took place from September 2021 to July 2022. A cluster sampling method was used to select 60 full-time nursing students from a school in China, and randomly divide them into a control group of 36 and an experimental group of 24. According to the principle of voluntary participation, 6 students majoring in clinical medicine and 6 students majoring in pharmacy were recruited to join the experimental group to form an interprofessional team. The students studied "Clinical Critical Thinking Training" together, in which the control group used traditional simulation teaching and the experimental group used SIPE. The CCTDI (California Critical Thinking Disposition Inventory) and AITCS-II Student (Assessment of Interprofessional Team Collaboration in Student Learning Scale) were used for quantitative evaluation before and after the course, and descriptive statistics and Mann-Whitney U test were used to compare the critical thinking and interprofessional collaboration skills of the two groups of students. Semi-structured interviews were used for qualitative evaluation. Thematic analysis was used to understand student development on the basis of inter-professional core competencies and learning experience. Results The students' interprofessional cooperation abilities and critical thinking scores improved compared with the beginning of the course, but the scores of the experimental group were significantly higher than the control group (p < 0.05). Three themes emerged regarding simulated interprofessional teaching: clarifying team positioning, improving team efficiency, and optimizing the learning experience. Conclusion SIPE can build students' critical thinking, teamwork, and interprofessional core competencies, which makes it a useful teaching design.